(untitled) (Conferencea, 2022)
This scientific thesis briefly reveals the features of the development of the media in Uzbekistan, taking into account the trends of informatization of modern society. The characteristics of the development of regulatory regulation of the activities of the media, the role of the media in the development of the information society are carried out. The final conclusion in the thesis is the statement about the need to regulate the legal status of the blogger in the Republic of Uzbekistan..